KONSEKUENSI YURIDIS BAGI NOTARIS DAN PARA PIHAK TERKAIT ADANYA PEMUNGKIRAN TANDA TANGAN ATAS SURAT BAWAH TANGAN YANG DILEGALISASI - MORIA GUNAWATY (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. T. Keizerina Devi A3. Suprayitno The role of a Notary is very important in giving legal certainty, especially civil case since people today need authentic written evidence. Therefore, a Notary has to be cautious in doing his job because it is not uncommon that a Notary is summoned by the Court. One of the causes is that there is a denial of the signature on a legalized underhanded certificate. The certificate has to provide legal certainty, especially about the date and the signatures of the persons appearing. However, the problem arises when some of them deny their signatures. The research problems are how about the procedure of legalization of an underhanded certificate, how about legal consequence of stakeholders concerning denial of signatures on a legalized underhanded certificate, and how about some measures which have to be taken by a Notary to prevent from denial of signatures.Keywords: Denial of Signature, Underhanded Certificate, Legalization